Pengaruh Model Discovery Learning Terhadap Keterampilan Proses Sains Dan Hasil Belajar Siswa Pada Materi Makanan Dan Sistem Pencernaan Di SMP Imelda Medan - Riski Hotma Oktaviani; Ely Djulia; Tria Gayatri (Program of Biology Education, Universitas Lambung Mangkurat, 2026)
This study aims to determine the effect and correlation of applying the discovery learning model on students’ science process skills and learning outcomes regarding food and the digestive system at Imelda Private Junior High School in Medan. This study uses a quantitative approach Pretest-Posttest group design. The instrument used in this study was a learning outcome test consisting of 20 multiple-choice questions with a reliability value of 0.851. The data analysis techniques used were normality test using Shapiro Wilk, homogeneity test, hypothesis test using the right-tailed t-test, and N-Gain test. The results of the observation of science process skills obtained all indicators of science process skills have a very high category. The average learning outcome of the experimental class is 76.04. Higher than the control class which is 70.83. The results of the right-sided t-test with a significance level of α = 0.05, obtained tcount> ttable, namely 1.84> 1.65. The N-Gain value on learning outcomes is 62.45. The results of the study indicate that the application of the Discovery Learning model has a significant effect on science process skills and student learning outcomes on food and digestive system materials.